Every woman a theologian : know what you believe : live it confidently : communicate it graciously - Masonheimer, Phylicia (W Publishing Group, an imprint of Thomas Nelson, 2023)
"Know what you believe and live it boldly! Phylicia Masonheimer believes that every woman should be a theologian and a student of the heart of God. Learn the basics of theology and why it's so important, continuing your biblical education one step at a time. Discover how deeper scriptural knowledge can help you navigate the world, answer your toughest questions, and engage culture in loving ways. All of us have guiding principles at work behind our choices, even if we don't realize it. We hold beliefs about the world, ourselves, and God-beliefs perhaps we may have adopted unknowingly based on experience or culture's messages. But God has revealed Himself through Scripture so it can transform how we view and navigate the world-how we think, act, love, work, marry, and parent. When we do that, we become theologians. No, we're not wearing tweed suits or giving lectures; we're driving to our corporate job every morning, or juggling babies on our own, or connecting with our communities. We're women want to know who God is and how He answers our toughest questions. Through engaging stories and compelling truths, Every Woman a Theologian will help you identify your existing beliefs about God, salvation, and the Christian life; learn how to lovingly communicate Christian truths to those who disagree; understand theological concepts without feeling overwhelmed; grow closer to the heart of God. With Phylicia Masonheimer as your guide, you will grow as a woman able to discern truth, who knows what she believes, and who lives her faith boldly in a post-Christian world"--